613 The Floating Hip: A Distinct Injury Pattern? A Descriptive Study and Case-Control Analysis. (12th October 2021) - Wong, M; Ghobrial, M; Han, W M; Alsousou, J; Chou, D; Carrothers, A; Hull, P; Rawal, J
Abstract: Aim: A "Floating Hip" injury describes a simultaneous ipsilateral fracture of the femur and pelvis. We performed a descriptive study of the injury patterns, management, and outcomes of floating hip patients, and compared these patients to those with similar pelvic fractures without femoral involvement. Method: This was a retrospective case-series review with secondary case-control analysis. Medical records of patients presenting with a floating hip injury to our tertiary orthopaedics department between 2015 and 2020 were reviewed. The control group comprised of patients with pelvic fractures but without associated femoral fractures, matched by age, sex, pelvic fracture classification, and mechanism of injury. Results: 46 Floating Hip cases were identified (34 males), of average age 39 (15-86) years. 20 had acetabular fractures, 21 had pelvic ring fractures and 5 had both fractures, concomitant with ipsilateral femoral fractures. The most common site of femoral fracture was mid-shaft (21.7%), followed by distal (19.6%). 69.6% of P/A fractures were managed surgically, with ORIF (43%) the most common option. 4 (12.50%) patients suffered complications, including 2 infections and 1 DVT. Compared to controls, Floating Hip patients were more likely to require surgical management (67.6% vs 47.8%, p = 0.03), and had higher rates of surgical complications (12.5% vs 4.6%), though not statistically significant (p = 0.3). Conclusions: Our study describes the patterns, management, and outcomes of Floating Hip injuries, and observes differences in the management and complications compared to similar pelvic fractures without femoral involvement. These findings suggest Floating Hip cases may warrant consideration as a distinct injury pattern.